Rancang Bangun Aplikasi E-Commerce Pada UMKM Berbasis Web Sebagai Strategi Pengembangan Pasar (Studi Kasus: Resto Ayam Bakar Rafi) - Ahmad Ropii Abdilah; Erdi Sutriyatna (Teknik Informatika Universitas Pamulang, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in supporting Indonesia's economic growth, but they still face challenges in reaching a wider market. Digitalization through website development is an effective solution to increase the competitiveness and sales of MSMEs. This study aims to design and develop the Rafi Grilled Chicken Restaurant website using the Extreme Programming method. The Extreme Programming method includes planning, design, coding, and testing. The planning stage was conducted through interviews and observations to identify user needs. The analysis resulted in key features such as a menu catalog, an online food ordering system, and digital payment integration. The study showed that the developed website was able to improve operational efficiency and expand the restaurant's marketing reach. Based on the results of testing using a questionnaire, the system obtained an average score of 4.38, categorized as very good.